LAWS ON DIETETIC PRACTICES AND COMMUNICATION WITH PROFESSIONALS - Muangsri, Kanokpong; Tokaew, Wittayatorn; Sridee, Supaporn; Chaiyasit, Kamon (Journal of MCU Nakhondhat, 2023)
Dietetics is a profession that provides nutritional care to humans. It is one of the medical and public health disciplines that has emerged as a profession as a result of the Healing Arts Practices Act, B.E. 2542. As a result, relevant legislation was enacted to regulate the professionals responsible for providing healthcare and nutrition to patients. Not only does professional law apply to the art of healing practices, but so do the Criminal Code, the Civil and Commercial Code, and the determination of compensation for damages arising from professional practices that violate patients’ rights. The Professional Committee also considers administrative sanctions, which may include warnings, license suspension, or license revocation. Dietetic practice is regarded as a public health service and consequently bound by consumer protection laws as well as the Medical Facilities Act and the practice establishments that regulate the roles and responsibilities of professionals. As a result, professionals must prioritize patients and exercise caution in performing their duties in accordance with professional ethics and standards. Communication to enhance knowledge and awareness of relevant laws is critical for safe dietetic practice for both professionals and patients.